PENGARUH METODE PEMBELAJARAN HAFALAN KITAB NADHAM IMRITHI TERHADAP PENGUASAAN ILMU NAHWU DI MTS SAYYID ABDURROHMAN PAGERWOJO PERAK JOMBANG - astrid dwi firliana inayati (Universitas KH. A. Wahab Hasbullah, 2019)
ABSTRACT Methods are ways or steps used in conveying ideas while memorizing, according to the KBBI, said basic memorization that can be said by heart (without looking at books or other notes). Based on this understanding, it can be stated that mastery is understanding. Understanding not only means knowing the nature of remembering (memorization), but is able to express it again in another form or in its own words so that it is easy to understand the meaning of the material being studied, but does not change the meaning that is in it. The problem to be investigated is whether there is the influence of the Nadham Imrithi Book Memorization Learning Method on Nahwu Science at MTs Sayyid Abdurrohman Pagerwojo Perak Jombang.This study aims to describe: 1) the implementation of rote learning methods in MTs Sayyid Abdurrohman Pagerwojo Perak Jombang. 2) mastery of nahwu material in Mts Sayyid Abdurrohman Pagerwojo Perak Jombang. 3) the effect of rote learning methods on the mastery of nahwu science at MTs Sayyid Abdurrohman Pagerwojo Perak Jombang.This type of research is field research (Fled Research) through a correlational quantitative approach. The method of determining the subject takes all class VIII, and Class IX at MTs Sayyid Abdurrohman Pagerwojo Perak Jombang as research respondents totaling 50 students. While the method I use in this study is a quantitative method, with data collection techniques including: observation, interviews, documentation and questionnaires. Data analysis uses the product moment correlation formula. The hypothesis proposed is Ha: there is the influence of rote learning methods on the mastery of nahwu science.The results of the interpretation of the data obtained are r count> r table (0.287> 0.2500) so that Ha states that there is an influence of rote learning methods on mastery of nahwu science at MTs Sayyid Abdurrohman Pagerwojo Perak Jombang otherwise accepted.